Recruitment System of Lecturers at Islamic University in Indonesia: Head of Departement Perspective - Adib Susilo; Sheema Haseena Armina; Meichio Lesmana (Islamadina : Jurnal Pemikiran Islam, 2021)
ABSTRACTThis research is aimed to investigate how recruitment process conducted in Islamic university and what is the head of department policy in Islamic university in on recruitment process and in maintaining the quality of lecturer. A phenomenology approach was adopted. Data were gathered by conducting interviews with five participants which all is head of department (HOD) at Islamic universities in Indonesia. The data analyzed with grounded theory through three steps coding namely, open coding, axial coding and selective coding. The research found five themes related to recruitment process at Islamic university, namely main recruitment stages, recruitment types, applicant selection, recruitment problems and HOD decision. This research was aimed to seek the recruitment process at Islamic university. The future research should examine the impact of recruitment to the lecturer performances. The findings resulted in two implications. Theoretically, it is found that Islamic University had a unique distinction in recruitment process which is based on value and philosophy of the university. Practically, HOD decision in recruitment process should not be interfered, if there are potential candidate should be discussed in senate forum. This research focused on the recruitment process of lecturer at Islamic university and HOD policy on recruitment.Kata kunci : Recruitment process, Islamic university, head of Department policy, philosophy of university